Evaluating the efficacy and tolerability of the oral combination of alpha lipoic acid and vitamin B complex preparation in carpal tunnel syndrome: a single center, randomized, double-blind, placebo-controlled trial - Zainal, Nur Alya; Abdul Rashid, Anna Misya’il; A. Rauf, Adnan Lutfi; Yusof Khan, Abdul Hanif Khan; Wan Sulaiman, Wan Aliaa; Basri, Hamidon (BioMed Central, 2025)
Background: Carpal Tunnel Syndrome (CTS) is the most common type of nerve entrapment and can cause significant disability by impairing hand functionality. This study aims to evaluate the efficacy and tolerability of an oral combination of alpha-lipoic acid (ALA) and vitamin B complex in alleviating CTS symptoms and improving the quality of life in patients with mild to moderate CTS. Method: A total of 70 patients with mild to moderate CTS were enrolled in this study at Hospital Sultan Abdul Aziz Shah, Selangor, Malaysia. Using a double-blind Randomized Controlled Trial (RCT) design, participants were randomly assigned to either the treatment group (n = 37) or the placebo group (n = 33). The treatment group received two tablets once daily containing alpha-lipoic acid (300 mg), methylcobalamin (500 mcg), vitamin B1 (39 mg), and vitamin B6 (8 mg) i.e. Bionerv while placebo group received combination of maltodextrin, microcrystalline cellulose, tricalcium phosphate, silicon gioxide, magnesium stearate; two tablets once daily for 6 months. Patients were evaluated across three visits: baseline (Visit 1), 3 months (Visit 2), and 6 months (Visit 3). During each visit, patients were evaluated using three assessments. The three assessments included three standardized questionnaires: SF-36, VAS, and BCTQ, Nerve Conduction Study (NCS) and Patient-Reported Questionnaire to monitor any side effects. Results: A significant improvement in VAS scores was observed in the treatment group, indicating better pain control. However, no statistically significant differences were found between the treatment and placebo groups in other outcome measures, including SF-36, BCTQ, and NCS parameters. While improvements in SF-36 and BCTQ scores were noted in the treatment group, these changes did not reach statistical significance and should be interpreted as a positive trend rather than definitive evidence of efficacy. The combination of alpha-lipoic acid and vitamin B complex was well tolerated, with most participants reporting minimal and self-limiting adverse effects. The most common side effects were mild gastrointestinal symptoms, such as abdominal discomfort and diarrhea, which resolved upon discontinuation of drugs. Conclusion: The oral combination of alpha-lipoic acid and vitamin B complex (Bionerv) demonstrated potential pain relief benefits in patients with mild to moderate CTS and was found to be well tolerated. Future studies with larger sample sizes are recommended to strengthen the findings and provide more comprehensive insights.